Interpretation of the Verses of the Obligation to Study - Muhammad Thuba; Iskandar Mirza (Penerbit Hellow Pustaka, 2025)
Learning is crucial in all aspects of life, as it serves as the foundation for every achievement. For Muslims, practicing Allah's commandments correctly and in accordance with Sharia rules also requires knowledge, which begins with learning. Due to the significance of learning, the author will discuss the obligation to learn by referring to the ultimate source of knowledge, which encompasses the wisdom of past and future generations (‘ilm al-awwalin wa al-akhirin). The author will examine several Quranic verses that emphasize the obligation of learning, employing a simple literature-based approach. Relevant Quranic verses will be analyzed using classical exegesis as the primary reference, complemented by contemporary studies.